What Affects the Quality of Pharmacovigilance? Insights From Qualitative Comparative Analysis - Yadong Wang; Yue Chen; Xingjuan Xu; Ting Ying; Runan Xia; Yuanyuan Zhang; Xuefeng Xie (Pharmacology Research & Perspectives)
ABSTRACT Pharmacovigilance plays a significant role in guaranteeing the safety of medications for patients. Over the last three decades, China has significantly advanced its pharmacovigilance practices, yet the factors that drive the quality of pharmacovigilance remain unclear. This study aimed to investigate how multiple factors interactively influence the quality of pharmacovigilance and identify pathways for achieving high‐quality pharmacovigilance practices. A unique sample of pharmacovigilance‐specific inspection reports from 13 representative companies in China was adopted in analysis. Given the qualitative nature of the inspection reports, we utilized crisp‐set qualitative comparative analysis (csQCA) with five factors structure based on the technology–organization–environment (TOE) theoretical framework. The csQCA enabled us to elucidate the interactions among the antecedents of pharmacovigilance quality through quantitative univariate necessity analysis and configuration analysis. Three pathways contributing to high‐quality pharmacovigilance were identified, and “Dedicated and Qualified Person for Pharmacovigilance (DQPPV)” was shown to be involved in all three pathways. Upon examining the manner in which multiple variables influence the quality of pharmacovigilance, it becomes evident that the DQPPV represents a factor that warrants further investigation. The results of the configuration allow companies to implement targeted measures to enhance the functionality of the pharmacovigilance system and to improve the quality of the system. Further research could explore the influence of additional factors on pharmacovigilance efforts, which could then contribute to marketing authorization holders' (MAHs') pharmacovigilance efforts.